The digital escape room developed for nursing students: GestDia - Ilknur Atasever; Afra Calik; Emel Tasci Duran (BMC Medical Education)
Abstract Background Digital escape rooms have been developed during the pandemic, which improves students’ cooperation, communication skills, and critical thinking skills, effects on learning in nursing education. Method This study aimed to evaluate the GestDia escape room to assess students’ motivation and self-confidence in learning. A descriptive quantitative interventional study was carried out. The study population was nursing students in their third semester (n = 45). The students filled out the Instructional Materials Motivation Survey and Student Satisfaction and Self-Confidence in Learning Scale. Results The mean scores obtained from motivation, satisfaction, and self-confidence scales were generally higher. Males scored higher on all scales than females, though these differences were not statistically significant (p > 0.05). Conclusion In general, although games increase students’ motivation, satisfaction, and self-confidence, they can lead to gender differences. In the digital world, integrating escape rooms into nursing education can add joy to students’ learning process.